ASSESSMENT OF BIOCHEMICAL AND IMMUNOLOGICAL FEATURES IN BURN DISEASE BASED ON SEVERITY STAGES (Scientific Conference on Multidisciplinary Studies, 2025)
Currently, thermal injuries rank third among all types of trauma worldwide. According to the World Health Organization (WHO), burns are the third most common type of injury. In general, burn injuries affecting more than 10-15% of the body surface are associated with burn disease (BD) and the development of systemic inflammatory response syndrome (SIRS), which often leads to multiple organ dysfunction syndrome (MODS). The role of immunodeficiency in BD has become a major focus of modern research, as both innate and adaptive immune responses exhibit early and prolonged suppression. To assess the severity of burn disease, it is essential to evaluate biochemical and immunological parameters. These indicators are crucial in determining the severity of the injury and the adequacy of the treatment strategy.